A categorization of recent network approaches to analyse trophic interactions. Issue 10 (14th August 2013) - Miranda, María; Parrini, Francesca; Dalerum, Fredrik; Giuggioli, Luca
Summary Network analysis, a branch of discrete mathematics that quantifies the structure of links between a set of nodes, is emerging as a powerful methodology to approach complex ecological interactions. There has been a rapidly increasing body of research targeting the topological description of trophic interactions. Here we categorize studies applying a topological approach to empirical trophic networks, with the aim of identifying recent trends and deficiencies in this approach to analyse trophic interactions. There were biases in the taxonomic groups addressed and in the methodological approaches used for data collection and analyses. Studies on antagonistic interactions were generally focused on a single kind of bipartite interaction, and most studies compared network attributes across time, ecosystems or treatments. We encourage a broader use of both interlinked and unipartite networks that would allow for describing indirect effects of trophic interactions, as well as time series of networks across seasons and phenological states of organisms. We also noted shortages of studies identifying interaction structures across levels of organization, on the correspondence between network structure and function, and particularly of studies on the behaviour of trophic networks in the face of environmental perturbations, which could provide guidance for preserving ecological interactions.